Two Way Street – Public Health and Transportation Working Together on Active Transportation. (June 2018) - Mele, Lorenzo; Loh, Lawrence
Abstract : The link between health and transportation systems is well described, and numerous studies explore health benefits associated with active transportation. This paradigm shift is addressed in a range of transportation strategies, plans and technical guidelines, including public health campaigns and programming. Despite this increased focus, public health and transportation sectors face challenges common to other inter-sectorial efforts, including different skills, perspectives, expectations, and scenarios of practice. Evaluation and analysis of effective models of engagement between these two sectors would maximize public health and transportation collaborations to reach active transportation goals. In 2015, the Ontario Public Health Association – Built Environment Work Group conducted a research project entitled "Two Way Street - Public Health and Transportation Working Together on Active Transportation." The objective of this review was to better define various challenges and opportunities to strengthen public health and transportation collaboration, with a detailed focus on the perspectives of transportation professionals on perceived barriers to improving infrastructure towards better promoting active transportation. The review involved a scan of documents, stakeholder mapping, and in-depth semi-structured interviews with transportation professionals. The resulting themes identified key areas in which public health and transportation could support each other. Chief among these was defining public health's support - role and practice in Environmental Assessment (EAs) and land development approval processes. This insight prompted the OPHA-BEWG to carry out a subsequent survey of Public Health Units (PHUs) in the province of Ontario in Canada to assess their involvement with EAs for transportation. The study found that while most PHUs desired greater involvement in the EA process; specific barriers resulted in only a small portion of PHUs in the process. Respondents suggested capacity building by sharing and refining assessment tools, creating webinars and workshops, and online resources with detailed information on best practices. Further, PHUs in rural communities highlighted a need for approaches that acknowledge settings with low population density, expansive landscapes, and dispersed populations for improving active and sustainable transportation. The session will review the detailed findings and best practices identified through this work, and conclude with a knowledge sharing activity to stimulate discussion among participants on initiatives already undertaken in their public health work to advocate for active transportation. Through this activity, it is anticipated that participants will gain insight from a variety of perspectives and the opportunity to develop a network of professionals within public health and transportation committed to sharing resources, ideas, and taking action.